Development of Teaching Materials for Popular Scientific Articles Using Contextual Approach for Grade VIII Students - Alhafidz, Zidan Rizka; Ekawati, Mursia; Jendriadi, Jendriadi (Jurnal Paedagogy, 2025)
This study aims to develop a popular scientific article teaching book based on a contextual approach for eighth-grade students. The research method used is Research and Development (R&D) with the 4D model, limited to the development stage. The research subjects involve teachers and eighth-grade students from MTs Negeri 1 Kota Magelang, with feasibility assessments conducted by two subject matter experts and two media experts. Data analysis used quantitative descriptive techniques through the calculation of the average expert validation score, supported by qualitative analysis of improvement suggestions. The results show that the developed textbook received a 'highly suitable' category, with scores of 95.3% from subject matter experts and 96.6% from media experts, resulting in an overall average of 95.9%. Therefore, the textbook is deemed highly suitable for use as a learning support tool for popular scientific article texts in junior high schools/MTs.